Dynamic trajectory for landing an aerial vehicle on a mobile platform. Issue 14 (2022) - Alatorre, A.; Cariño, J.; Castillo, P.; Lozano, R.
Abstract: In the presented work, a trajectory is designed allowing an Unmanned Aerial Vehicle (UAV) to perform landing on a mobile platform. The proposed trajectory behaves in such a way that grants a seamless integration of information about the target landing platform into its design. This allows any generic tracking controller to follow the trajectory regardless of the target's dynamics or movement, as they are indirectly applied to the trajectory's architecture. The focus of this work is for fixed-wing aircraft to land on water surface vehicles but can be adjusted for different scenarios. One of which is used for the experimental corroboration of the proposed strategy in a real-world environment.